2019
DOI: 10.1136/bmjopen-2019-029290
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Lifestyle Program (HeLP) for low back pain: protocol for a randomised controlled trial

Abstract: IntroductionLow back pain is one of the most common and burdensome chronic conditions worldwide. Lifestyle factors, such as excess weight, physical inactivity, poor diet and smoking, are linked to low back pain chronicity and disability. There are few high-quality randomised controlled trials that investigate the effects of targeting lifestyle risk factors in people with chronic low back pain.Methods and analysisThe aim of this study is to determine the effectiveness of a Healthy Lifestyle Program (HeLP) for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…However, the studies have examined the relationship between health practices and physical health status, but not the musculoskeletal symptom outcome. Recently, changing patterns of daily life activities into a healthy lifestyle (e.g., achieve a healthy body weight, increase physical activity, develop healthy eating habits, quit smoking) has been used in interventions for low back pain ( Robson et al, 2019 ). However, it was not clarified which lifestyle changes should be prioritized.…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies have examined the relationship between health practices and physical health status, but not the musculoskeletal symptom outcome. Recently, changing patterns of daily life activities into a healthy lifestyle (e.g., achieve a healthy body weight, increase physical activity, develop healthy eating habits, quit smoking) has been used in interventions for low back pain ( Robson et al, 2019 ). However, it was not clarified which lifestyle changes should be prioritized.…”
Section: Introductionmentioning
confidence: 99%
“…28 Several studies identified that people with increased BMI and unhealthy lifestyles, including lack of physical activity and inappropriate diet, were more likely to suffer from chronic LBP. 36,37 A study by Li et al demonstrated that due to a high workload and less leisure time, nurses are practicing unhealthy dietary habits and inadequate physical activity, which are known significant drivers of increased BMI and LBP itself. 26 The nationwide survey is needed to uncover the significant stressors of LBP among nurses, which could provide the platform for the development of effective policy, plans, and interventions to prevent LBP and its complications among Chinese nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Mekhail et al (2018) presented a one-year follow-up in which current smokers reported a numerical rating scale pain score of 7.0, which is 1.93 (p < 0.001) and 1.32 (p = 0.001) points higher than those of lifelong nonsmokers and former smokers, respectively [19]. Robson et al (2019) started a study with the aim of determining the effectiveness of a Healthy Lifestyle Programme (HeLP) for low back pain, targeting weight, physical activity, diet and smoking, to reduce disability in patients with chronic low back pain, compared with usual care. The outcomes of this trial and supplementary analyses will be disseminated through publications in peerreviewed journals and conference presentations [20].…”
Section: Discussionmentioning
confidence: 99%